2015
DOI: 10.1149/06914.0017ecst
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Nanopores and Formation of Nanoporous Domains during Anodization of n-InP in KOH

Abstract: Anodization of highly doped (1018 cm-3) n-InP in 2 – 5 mol dm-3 KOH under potentiostatic or potentiodynamic conditions results in the formation of a nanoporous sub-surface region. Pores originate from surface pits and an individual, isolated porous domain is formed beneath each pit in the early stages of anodization. Each such domain is separated from the surface by a thin non-porous layer (typically ~40 nm) and is connected to the electrolyte by its pit. Pores emanate from these points along the <111>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…2a. It is reported that pits can be prepared via defect-related electrochemical etching 14,17 . Due to the interface curvature effects and the high electric field…”
Section: Resultsmentioning
confidence: 99%
“…2a. It is reported that pits can be prepared via defect-related electrochemical etching 14,17 . Due to the interface curvature effects and the high electric field…”
Section: Resultsmentioning
confidence: 99%
“…The electrode area was typically 0.5 cm 2 . InP wafers with carrier concentrations from 3.410 18 to 6.710 18 cm -3 and etch pit densities of less than 500 cm -2 were ECS Transactions, 77 (4) 67-96 (2017) used. Anodization was carried out in aqueous KOH electrolytes of 5 mol dm -3 .…”
Section: Methodsmentioning
confidence: 99%
“…It is generally accepted that this limited hole supply is what causes the initiation and propagation of porous etching, with hole supply being enhanced (and hence, porous etching initiated) at defect sites at the surface [6]. The newly formed pore tips then act as sites for the continuous preferential supply of holes [7]. However, the variation in feature size, as well as the morphology observed, as experimental conditions are varied cannot be so readily explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Due to the differing etch rates of crystal planes, the formation of tetrahedral etch pits (seen as dove-tailed and v-groove voids, respectively in (011) and (011) cross sections) is observed on the (100) surface of III-V semiconductors. 1,2,38,43,44 We have previously shown that anodization of an n-InP electrode in >2 mol dm −3 KOH results in the formation of a nanoporous InP layer 3,[48][49][50][51] of finite thickness. [52][53][54][55][56] Further investigation showed that the porous region is capped by a thin layer (20-40 nm, depending on the conditions) close to the surface that appears to be unmodified.…”
mentioning
confidence: 99%